The DTN Routing Algorithm Based on Markov Meeting Time Span Prediction Model. (18th September 2013) - Wang, En; Yang, Yongjian; Jia, Bing; Guo, Tingting
Putting forward an efficient routing algorithm in DTN (delay tolerant network) has become a focus of attention due to the existing phenomena that the connections between nodes in the network change dramatically over time and the communications suffer from frequent disruptions. In this paper, the meeting time span between nodes is predicted using the Markov model, and the relay node holding the shortest meeting time span with the destination node is determined as the most efficient node. In the two phases, spray phase and wait phase, the message is routed according to the utility value. Thus, the routing algorithm based on Markov meeting time span prediction model is provided. Simulation results suggest that this algorithm efficiently improves the delivery rate and reduces the average delay.